Identifikasi dan Aplikasi Marka Berbasis PCR untuk Identifikasi Varietas Padi dengan Palatabilitas Tinggi - Lestari, Puji; Risliawati, Andari; Koh, Hee Jong (Jurnal AgroBiogen, 2012)
To date, there hasbeen no DNA fingerprint profile as unique identity of ricevariety that has a high palatability (overall eating quality) inIndonesia, thus identification of premium varieties usingmolecular markers is considered to be important. This studyaimed to establish DNA fingerprint profiles of indica andjaponica rice varieties, and unique identities of rice varietieswith high palatability using molecular markers associatedwith palatability. Total of 22 japonica and 24 indica ricevarieties were evaluated their overall eating quality andtested using 20 molecular markers STS (sequence-taggedsite) which were designed on the basis of japonica ricegenome. To identify the genes functions, all these markersamplicons were cloned, transformed, sequenced and thesequences results were analyzed their homologous againstthe genome database. Ilpum (japonica) and Rojolele(indica) were identified to have the highest palatabilitycompared to other varieties. DNA fingerprint profilesidentified with the total STS markers were not able todifferentiate each variety, however premium varieties ofjaponica and indica showed specific identities. A uniqueidentity of Indonesian indica variety possessing highpalatability, Rojolele was successfully developed using amarkers set. DNA fingerprint profile in digital value systemfacilitates the identification of premium rice from othervarieties. The fragments of the STS primers showed no anyknown-genes functions related to rice eating quality,therefore these markers are preferentially used foridentification of premium rice with high palatability thandifferentiation of rice varieties based on the palatability. Inthis study, the unique identity of rice variety with highpalatability is very usefull to evaluate the purity forgermplasm protection.